2013
DOI: 10.6007/ijarems/v2-i4/155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of barriers to entrepreneurship in Small and Medium-sized Enterprises (SMEs)

Abstract: Today entrepreneurship is considered as the economic driving engine for developed and developing countries and most countries have invested considerably on entrepreneurship development. The entrepreneurship development in a community could provide sustainable employment and economic development. It should be noted that entrepreneurship development has always been encountered different challenges and barriers. The present article is aimed to detect and classify the barriers of entrepreneurship development in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Likewise, the respondents from various age groups were similarly inspired by internal motives when planning their own business to a larger extent than by the external ones. Similar to other studies (Jafarnejad, Abbaszadeh, Ebrahimi, & Abtahi, 2013;Sharma & Madan, 2013;Smith & Beasley, 2011;Staniewski, 2009;Tanveer et al, 2011), our findings revealed that people who plan to start their own businesses perceive numerous burdensome obstacles. In the opinion of our respondents, the most harmful barriers were lack of experience, lack of capital and risk of failure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, the respondents from various age groups were similarly inspired by internal motives when planning their own business to a larger extent than by the external ones. Similar to other studies (Jafarnejad, Abbaszadeh, Ebrahimi, & Abtahi, 2013;Sharma & Madan, 2013;Smith & Beasley, 2011;Staniewski, 2009;Tanveer et al, 2011), our findings revealed that people who plan to start their own businesses perceive numerous burdensome obstacles. In the opinion of our respondents, the most harmful barriers were lack of experience, lack of capital and risk of failure.…”
Section: Discussionsupporting
confidence: 91%
“…Among the barriers, students indicate a lack of professional experience and funding (Staniewski, 2009), lack of skills, lack of assistance, lack of capital, lack of awareness, and fear of the future (Tanveer et al, 2011). In turn, entrepreneurs from the SME sector recognise that the most important barriers and challenges are lack of sufficient knowledge of management skills, lack of adequate investment to start and run a business, difficulty in discovering information about markets, products and prices, troublesome rules, obtaining bank loans, and difficulty in recruiting good and reliable staff (Jafarnejad, Abbaszadeh, Ebrahimi, & Abtahi, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second is the effect of social economic changes of the SSEs size-distribution in EA region on subsequent economic growth [29]. In case EA region has a larger share of small scale firms that could indicate a higher level of entrepreneurial activities.…”
Section: Entrepreneurship As a Major Factor Affecting Youth Employmentmentioning
confidence: 99%
“…On the other hand, women have a higher fear of failure in entrepreneurial activities than men. In other studies, such as the one carried out by Jafarnejad et al (2013), Sharma and Madan (2013), Tanveer et al (2011), the authors focus first and foremost on barriers preventing entry into entrepreneurship. Their results show that the question of barriers in entrepreneurship remain open for discussion.…”
Section: H3: There Is a Difference Between The Perspectives Of Men Anmentioning
confidence: 99%